(untitled) (International Journal of Contemporary Security Studies, 2024)
In Poland, facial recognition for public security purposes is a matter subject to various legal acts. The aim of the paper is to indicate the legal acts that regulate these issues, the way in which Poland approaches data protection in the context of the use of recognition systems, as well as the way of harmonizing with European guidelines. The paper offers a continuation of the discussion on the need to ensure the security of the state in accordance with the basic rights and freedoms of citizens using this technology.